2021
DOI: 10.1002/aelm.202100313
|View full text |Cite
|
Sign up to set email alerts
|

Direction‐Selectable Ultra‐Highly Oriented State of Donor–Acceptor Conjugated Polymer Induced by Slow Bar Coating Process

Abstract: The molecular orientation of π‐conjugated polymers is a significant factor for the electrical properties of polymer‐based printable devices, because π‐conjugated polymers exhibit a notable fast carrier transport property along their main chain. Although various coating processes are suggested, the challenge to realize high‐degree alignment by one‐step coating without pre‐ or post‐treatments still remains. In this paper, it is reported on the fabrication of an extremely highly aligned thin film by a slow bar co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 48 publications
(52 reference statements)
1
26
0
Order By: Relevance
“…The aggregate structure is important for the photoelectric conversion properties of optoelectronics applications. 22 On the other hand, the shape of the preaggregate seems to affect the molecular orientation, 20,23,24 which is significant for the carrier transport of thin-film transistors. The preaggregate tends to be a rod-like shape under certain conditions 9,25 and to be oriented by the fluid mechanical effect based on solution flow.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The aggregate structure is important for the photoelectric conversion properties of optoelectronics applications. 22 On the other hand, the shape of the preaggregate seems to affect the molecular orientation, 20,23,24 which is significant for the carrier transport of thin-film transistors. The preaggregate tends to be a rod-like shape under certain conditions 9,25 and to be oriented by the fluid mechanical effect based on solution flow.…”
mentioning
confidence: 99%
“…The preaggregate tends to be a rod-like shape under certain conditions 9,25 and to be oriented by the fluid mechanical effect based on solution flow. 24,26 D-A πconjugated polymers exhibit extremely high molecular orientation through a uniaxial coating method, such as bladecoating and bar-coating, 24,27,28 in comparison with the conventional π-conjugated polymers. The alignment state of the aggregate strongly contributes to the carrier mobility in the thin film, indeed.…”
mentioning
confidence: 99%
“…Some studies revealed that the alignment direction of molecular chains is decided by the relative strength of extension flow and shearing flow. When the shearing flow is dominant, the molecular chains are rotated and perpendicular to the coating direction. Notably, the difference in peak intensities of the parallel and perpendicular in the out-of-plane direction may be due to the measured positional deviation. In addition, the out-of-plane (010) peak position has a slight shift from 22.40° to 22.55° (Figure d).…”
Section: Resultsmentioning
confidence: 99%
“…In the study by Qu et al, they proposed that extensional flow and shearing flow are responsible for parallel alignment at the surface and perpendicular alignment at the bottom interface, respectively, which was later adopted by Yabuuchi et al to account for the orientation shift due to concentration. 41,54 In our present study, on the one hand, it is found that the dominant bulk alignment mirrors the surface alignment which indicates that shear flow at the bottom interface does not appear to be important. Instead of fibrils or chains aligning due to the influence of shear flow, in the low-P(NDI2OD-T2) blends, specifically 1.25 and 0.625% P(NDI2OD-T2), chain alignment may instead be templated by the evaporation front, with isolated fibrils/chains aligning parallel to the drying front as it passes across the sample.…”
Section: Charge Transport Properties Based On Ofetsmentioning
confidence: 99%
“…A similar result was also reported previously in a study by Yabuuchi et al, where they experimentally verified that the orientation condition was related to the initial concentration instead of the film thickness. 54 With regard to the second point, the perpendicular alignment in the present study cannot be the result of shear flow at the bottom interface. In the study by Qu et al, they proposed that extensional flow and shearing flow are responsible for parallel alignment at the surface and perpendicular alignment at the bottom interface, respectively, which was later adopted by Yabuuchi et al to account for the orientation shift due to concentration.…”
Section: Charge Transport Properties Based On Ofetsmentioning
confidence: 99%